2014
DOI: 10.1002/anie.201400533
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Induced Annihilation of Tumor Cells with Platinum–Porphyrin Conjugates

Abstract: Despite the extensive use of porphyrins in photodynamic therapy (PDT), tetraplatinated porphyrins have so far not been studied for their anticancer properties. Herein, we report the synthesis of such novel platinum-porphyrin conjugates as well as their photophysical characterization and in vitro light-induced anticancer properties. These conjugates showed only minor cytotoxicity in the dark, but IC50 values down to 19 nM upon irradiation with light at 420 nm.These values correspond to an excellent phototoxic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
155
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(157 citation statements)
references
References 44 publications
2
155
0
Order By: Relevance
“…This investigation will complement the well-known photochemistry of tetra(4-methylpyridinium)porphyrin com-plexes, [18] which have a charge of 4 + , as well as other PDT systems that we have recently reported. [19] Interestingly, James and co-workers have shown that tricationic porphyrins are taken up ten times better than tetracationic porphyrins by HT-29 cells. [20] In this study, we present the synthesis, characterisation and (photo)toxicity of novel porphyrins 2-4 against two human cancer cell lines (Scheme 1).…”
Section: Introductionmentioning
confidence: 98%
“…This investigation will complement the well-known photochemistry of tetra(4-methylpyridinium)porphyrin com-plexes, [18] which have a charge of 4 + , as well as other PDT systems that we have recently reported. [19] Interestingly, James and co-workers have shown that tricationic porphyrins are taken up ten times better than tetracationic porphyrins by HT-29 cells. [20] In this study, we present the synthesis, characterisation and (photo)toxicity of novel porphyrins 2-4 against two human cancer cell lines (Scheme 1).…”
Section: Introductionmentioning
confidence: 98%
“…26 In this work, we designed and synthesized fluorescent BODIPY-Pt conjugate (BODIPY-Pt), then studied its cellular uptake and cytotoxicities in human cervical carcinoma (HeLa) and human breast cancer (MCF-7) cell lines. The 1,3,5,7-tetramethyl-8-(4-pyridyl)-4,4′-difluorobora-diazaindacene (BODIPY) was synthesized according to the literature, 27 and BODIPY-Pt was prepared by using the reported method (Scheme 1) in 48% yield, 1,28 but using BODIPY as the imaging reporter. The structure of BODIPY-Pt was confirmed by proton nuclear magnetic resonance ( 1 H NMR) ( Figure S1) and matrix-assisted laser desorption/ ionization time-of-flight mass spectrometry (MALDI-TOF MS) ( Figure S2).…”
mentioning
confidence: 99%
“…8 To mimic the coordination interactions between PhenPt and DNA, several control experiments were performed. Guanosine triphosphate (GTP) was utilized as a competitive ligand to study the disassembly of the metallacycle M via fluorescence spectroscopy.…”
Section: Resultsmentioning
confidence: 99%